2019
DOI: 10.1111/acel.12955
|View full text |Cite
|
Sign up to set email alerts
|

NMNAT2‐mediated NAD+ generation is essential for quality control of aged oocytes

Abstract: Advanced maternal age has been reported to impair oocyte quality; however, the underlying mechanisms remain to be explored. In the present study, we identified the lowered NAD+ content and decreased expression of NMNAT2 protein in oocytes from old mice. Specific depletion of NMNAT2 in mouse oocytes disturbs the meiotic apparatus assembly and metabolic activity. Of note, nicotinic acid supplementation during in vitro culture or forced expression of NMNAT2 in aged oocytes was capable of reducing the reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 38 publications
5
90
0
2
Order By: Relevance
“…As Nampt acts via the salvage pathway to sustain cellular NAD 8 , we next asked whether Nampt-depletion impacted NAD levels. We measured NAD levels in oocytes as before 13 and found that they were significantly reduced following Nampt-depletion ( Fig. 6a) suggesting that reduced NAD availability might compromise asymmetry.…”
Section: Resultsmentioning
confidence: 96%
“…As Nampt acts via the salvage pathway to sustain cellular NAD 8 , we next asked whether Nampt-depletion impacted NAD levels. We measured NAD levels in oocytes as before 13 and found that they were significantly reduced following Nampt-depletion ( Fig. 6a) suggesting that reduced NAD availability might compromise asymmetry.…”
Section: Resultsmentioning
confidence: 96%
“…2f), suggesting that the subcellular localisation of NAD + biosynthesis is important for follicular and oocyte function. Given the subcellular localisation of NMNAT1 to the nucleus (21), this would suggest that nuclear NAD + synthesis is important to oocyte development, however another recent study demonstrated an important role for NMNAT2 in oocytes during ageing (22). To test the requirement for NAD + biosynthesis in maintaining normal oocyte function, we next treated GV stage oocytes with FK866, an inhibitor of the NAD biosynthetic enzyme NAMPT (23), and assessed meiotic progression (Extended Data Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, there may be signi cant heterogeneity between cells types and even among similar cells within a given tissue (e.g., due to local DNA damage or in ammatory foci) that are not resolved with our current methodology. In addition, impaired NAD + synthesis has been implicated in the aging of speci c cell types, including loss of tryptophan-dependent synthesis in macrophages (Minhas PS, 2019), loss of NMNAT-2 dependent synthesis in aged oocytes (Wu X, 2019), and diminished delivery of circulating NAMPT to the aging hypothalamus and peripheral tissues (Yoshida M, 2019). NAD + biosynthesis also drives developmental and reproductive processes (Crook M, 2014;Ear PH, 2019;McReynolds MR, 2017;Wang W, 2015) that are beyond the scope of the present study.…”
Section: Turnover Of Mitochondrial Nad +mentioning
confidence: 87%
“…Aged liver exhibits a signi cant decline in mRNA expression of Nmnat1 and trends towards lower expression of Nmnat2 and Nmnat3 (Camacho-Pereira, 2016). Similarly, expression levels of NMNAT isoforms are reduced in the kidneys, oocytes and colons of aged mice (Guan Y, 2017;Wu X, 2019;Zhu X, 2017). These observations suggest the alternative hypothesis that NAD + decline could be driven at least in part by decreased synthesis.…”
Section: Introductionmentioning
confidence: 84%